Thermal inactivation of Alicyclobacillus acidoterrestris spores isolated from a fruit processing plant and grape juice concentrate in South Africa - Groenewald, Willem H.; Gouws, Pieter A.; Witthuhn, R. Corli (Academic Journals, 2013)
Thermal inactivation at 95°C for two strains of Alicyclobacillus acidoterrestris isolated from contaminated fruit juice concentrates were investigated in a 0.1% (m/v) peptone buffer solution (pH 7.04) and grape juice (pH 4.02, 15.5 °Brix). The thermal inactivation of A. acidoterrestris spores followed first-order kinetics, suggesting that as the microbial population is exposed to a specific high temperature, the spores were inactivated at a constant rate. D-values determined in the buffer solution were calculated to be 1.92 ± 0.39 and 2.29 ± 0.50 min, while in grape juice D-values were found to be 2.25 ± 0.53 and 2.58 ± 0.32 min for the two strains tested.
Keywords: Alicyclobacillus acidoterrestris; Endospores; Thermal inactivation; Heat resistance; Spoilage; Fruit juice concentrate; D-value